Elasmopus alkhiranensis sp. nov., a new species of amphipod (Senticaudata, Maeridae) from the Persian Gulf - Myers, Alan; Momtazi, Farzaneh (Zootaxa, 2015)
A new species, Elasmopus alkhiranensis allied to E. pectenicrus is described from the Persian Gulf. Recent collections identify this species as having a morphological variation previously unreported in Elasmopus.